2021
DOI: 10.3390/ijerph18168413
|View full text |Cite
|
Sign up to set email alerts
|

Health Impact and Psychosocial Perceptions among French Medical Residents during the SARS-CoV-2 Outbreak: A Cross-Sectional Survey

Abstract: This study compared the impact on mental health and the psychosocial perceptions of medical residents and healthcare workers (HCWs) in a hospital after the first peak of the SARS-CoV2 outbreak in France. A validated version of the SATIN questionnaire with a modified scoring system was used to collect data on health and psychosocial factors. This questionnaire was sent to all workers at the hospital in July 2020 and was self-administered online. Using a multivariate multinomial regression model, the study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Such data have also been reported in other parts of the world [6,14]. We also found that being a medical resident leads to a risk of stress, mental health impacts, and a negative perception of the organizational context and work demands [15].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Such data have also been reported in other parts of the world [6,14]. We also found that being a medical resident leads to a risk of stress, mental health impacts, and a negative perception of the organizational context and work demands [15].…”
Section: Introductionsupporting
confidence: 86%
“…The occupational health service proposed a project that was accepted by all members of the hygiene and security committee. We assessed an online cross-sectional study of all professionals at the hospital [15,17]. The survey was conducted between 1 July 2020 and 31 August 2020 and involved all workers employed in a teaching hospital in France.…”
Section: Participantsmentioning
confidence: 99%